PENGARUH IKLIM ORGANISASI, PERILAKU KERJA DAN FUNGSI PENGAWASAN TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. BANK MANDIRI CABANG PEKANBARU SUDIRMAN ATAS DI KOTA PEKANBARU - Yani, Tri Indah; Wijaya, Errin Yani; ', Marnis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine how the effect of Organizational Climate, Work Behavior and Functions of Supervision to Job Satisfaction Employee at PT. Bank Mandiri Cabang Sudirman Pekanbaru. The population in this study were all employees of PT. Bank Mandiri Cabang Sudirman Pekanbaru with totaling 51 people, while the method of sampling is done by using saturation sampling methods and data analysis using multiple linear regression were processed with SPSS version 18.0. From the analyzing the data, simultaneous regression test (f-test) showed that Climate Organizational, Behavior Work and Functions of Supervision have effeect to Job Satisfaction Employee, while the partial test (t-test) Climate Organizational Behavior Work and Function of Supervision have effect on Job Satisfaction At PT. Bank Mandiri Cabang Sudirman Pekanbaru. The contribution of the influence of the independent variables (Climate Organization, Work Behavior and Function of Supervision) to the dependent variable (Employee Satisfaction) amounted to 86.4%. Companies should pay more attention gratification of the employee to work with the maximum example by observing Organizational Climate, Work Behavior and Function of supervision that exist in the company so that employees are more motivated to mendiptakan maximum performance.Keywords : Work Satisfaction, Climate Organization, Work Behavior and Function Supervision